1986
DOI: 10.1038/ki.1986.35
|View full text |Cite
|
Sign up to set email alerts
|

Tubulopathy in nephrolithiasis: Consequence rather than cause

Abstract: To address whether a renal tubular dysfunction is encountered in a particular patient subgroup with urolithiasis, the following parameters of tubular function were measured in urine taken in the morning from 214 stone formers after fasting: pH, excretion of lysozyme and gamma-glutamyl transferase (gamma-GT); fractional excretion (FE) of glucose, insulin, Mg, K, and HCO3 after an alkali loading; and the renal threshold for phosphate (TmP/GFR). The following diagnoses were made in the patient group: primary hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

1987
1987
2004
2004

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 35 publications
2
22
0
2
Order By: Relevance
“…Schardijn et al [14] and Musialik [15], who analyzed urinary β 2 m excretion, found that β 2 m values are similar in healthy people and in patients with active metabolic stone disease without UTI symptoms, whereas in patients with active metabolic stone disease and UTI, the excretion of β 2 m in the urine was 20-fold higher than in healthy subjects. This confirms the previous results of Jaeger et al [16] who suggested that in patients with nephrolithiasis a proximal tubule defect may be the result of an infectious process which is commonly related to the presence of stones in the kidney. An increased β 2 m excretion has been reported in patients with renovascular hypertension, in patients under hemodialysis or after renal transplantation, as well as in patients with UTI [12, 14, 15, 17].…”
Section: Introductionsupporting
confidence: 82%
“…Schardijn et al [14] and Musialik [15], who analyzed urinary β 2 m excretion, found that β 2 m values are similar in healthy people and in patients with active metabolic stone disease without UTI symptoms, whereas in patients with active metabolic stone disease and UTI, the excretion of β 2 m in the urine was 20-fold higher than in healthy subjects. This confirms the previous results of Jaeger et al [16] who suggested that in patients with nephrolithiasis a proximal tubule defect may be the result of an infectious process which is commonly related to the presence of stones in the kidney. An increased β 2 m excretion has been reported in patients with renovascular hypertension, in patients under hemodialysis or after renal transplantation, as well as in patients with UTI [12, 14, 15, 17].…”
Section: Introductionsupporting
confidence: 82%
“…Increased excretion of cellular enzymes has been observed in the urine of stoneforming humans (18,19) and of oxalate-loaded rats (20), and it has been postulated that cellular damage could result from crystal deposition. However, when the nephrotoxin gentamycin was administered to rats together with oxalate, crystal deposition was enhanced (31), suggesting that cellular damage might precede and promote crystal retention, rather than be a consequence of the crystals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies in stoneforming humans (18,19) and oxalate-loaded rats (20) have demonstrated that renal cellular injury occurs. In the current study, we defined the effect of diverse injuries to renal cells on crystal adhesion and how the PGE system might modulate this response.…”
mentioning
confidence: 99%
“…It has previously been ing stones [16][17][18][19][20]. Tubular dysfunctions can either be shown that tubular defects, expressed as incomplete a consequence of structural defects or caused by acidification disturbances and/or tubular proteinuria, hormonal or metabolic influence.…”
Section: Discussionmentioning
confidence: 99%